Until angels close my eyes - McDaniel, Lurlene (New York : Bantam Books, 1998)
Leah thinks her battle with cancer is over, but the disease that haunts her past has struck her kind and gentle stepfather. At first Leah is angry, but soon it turns to fear as she contemplates losing the first real family she's ever known.
Keywords: Terminally ill -- Fiction; Cancer -- PAtients -- Fiction; Teenagers and death -- Fiction; Love stories